Testing on A Diagnostic Test-based Science Metacognition Assessment Tool using Moodle - Dewi, Novi Ratna; Listiaji, Prasetyo; Savitri, Erna Noor; Yanitama, Arka (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
Metacognition is one of the important indicators of 21st century skills as part of ways of thinking. Metacognition ability is used by students to see how cognitive activities such as remembering, learning, and problem solving can be carried out effectively. However, in fact not many assessment tools have been developed to measure metacognitive ability. On the other hand, Moodle has good potential to be used as a platform for creating test instruments. The purpose of this study was to test a diagnostic test-based science metacognition evaluation tool that had been developed with Moodle. The research method used is quantitative by testing the validity, reliability, discriminating power, and level of difficulty on the items of the evaluation tool. The results showed that the science metacognition evaluation tool that had been developed had the characteristics of being valid according to experts, good reliability of 0.73, having a proportional difficulty index; and has good discrimination index. Based on the test results, it was concluded that the science metacognition evaluation tool had good characteristics in all aspects tested so that it was feasible to use it to measure students’ science metacognition abilities.